2016 IEEE Global Communications Conference (GLOBECOM) 2016
DOI: 10.1109/glocom.2016.7842028
|View full text |Cite
|
Sign up to set email alerts
|

Non-Orthogonal Unicast and Broadcast Transmission via Joint Beamforming and LDM in Cellular Networks

Abstract: Abstract-Research efforts to incorporate multicast and broadcast transmission into the cellular network architecture are gaining momentum, particularly for multimedia streaming applications. Layered division multiplexing (LDM), a form of nonorthogonal multiple access (NOMA), can potentially improve unicast throughput and broadcast coverage with respect to traditional orthogonal frequency division multiplexing (FDM) or time division multiplexing (TDM), by simultaneously using the same frequency and time resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…where n k ∼ CN(0, δ 2 1 ) is the addition noise caused by the ID. By using the layered division multiplexing, the common and private signal can be transmitted simultaneously [15]. At receiver, the user can decode the signals with successive interference cancellation.…”
Section: System Description and Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…where n k ∼ CN(0, δ 2 1 ) is the addition noise caused by the ID. By using the layered division multiplexing, the common and private signal can be transmitted simultaneously [15]. At receiver, the user can decode the signals with successive interference cancellation.…”
Section: System Description and Problem Formulationmentioning
confidence: 99%
“…which means that searching the root for the nonlinear equation T (q) = 0 is equivalent to solve (15). It can be found that T (q) is a strictly decreasing and convex function with respect to q, where T (q) > 0 with q → −∞ and T (q) < 0 with q → ∞.…”
Section: B Optimizing Digital Precoding and Power Splitting Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…More advanced solutions might further allow the overlay of broad-, multi-and unicast communications through nonorthogonal multiplexing/multiple access (NOMA), allowing for larger area broad-and multicast coverage, while supplying unicast traffic over the same resources [19]- [21]. If combined with time division multiplexing, such solutions may use NOMA to provide user data to users with high signal to noise ratio during time slots allocated for broadcast, without affecting broadcast quality -and thus allow effectively increasing network utilization.…”
Section: B Broad-and Multicast Distributionmentioning
confidence: 99%
“…On the one hand, NOUM has been envisaged as a recourse for improving spectral efficiency due to its capability of providing concurrent services in the same radio frequency resources. Specifically, NOUM has encountered outstanding solutions through layered-division-multiplexing (LDM) [1] and rate-splitting (RS) [2]. On the other hand, usage of the underexploited millimeter-wave spectrum is a promising solution to alleviate the scarcity of radio resources.…”
Section: Introductionmentioning
confidence: 99%